The SMART Registry: Long-Term Results on the Utility of the Penumbra SMART COIL System for Treatment of Intracranial Aneurysms and Other Malformations - Spiotta, Alejandro M.; Park, Min S.; Bellon, Richard J.; Bohnstedt, Bradley N.; Yoo, Albert J.; Schirmer, Clemens M.; DeLeacy, Reade A.; Fiorella, David J.; Woodward, B. Keith; Hawk, Harris E.; Nanda, Ashish; Zaidat, Osama O.; et al. (Frontiers in Neurology, 2021)
Introduction: Penumbra SMART COIL® [SMART] System is a novel generation embolic coil with varying stiffness. The study purpose was to report real-world usage of the SMART System in patients with intracranial aneurysms (ICA) and non-aneurysm vascular lesions. Materials and Methods: The SMART Registry is a post-market, prospective, multicenter registry requiring ≥75% Penumbra Coils, including SMART, PC400, and/or POD coils. The primary efficacy endpoint was retreatment rate at 1-year and the primary safety endpoint was the procedural device-related serious adverse event rate. Results: Between June 2016-August 2018, 995 patients (mean age 59.6 years, 72.1% female) were enrolled at 68 sites in the U.S. and Canada. Target lesions were intracranial aneurysms in 91.0% of patients; 63.5% were wide-neck and 31.8% were ruptured. Adjunctive devices were used in 55.2% of patients. Mean packing density was 32.3%. Procedural device-related serious adverse events occurred in 2.6% of patients. The rate of immediate post-procedure adequate occlusion (per Investigator) was 97.1% in aneurysms and the rate of complete occlusion was 85.2% in non-aneurysms. At 1-year, the retreatment rate was 6.8%, Raymond Roy Occlusion Classification (RROC) I or II was 90.0% for aneurysms, and Modified Rankin Scale (mRS) 0-2 was achieved in 83.1% of all patients. Predictors of 1-year for RROC III or retreatment (incomplete occlusion) were rupture status (P<0.0001), balloon-assisted coiling (P =0.0354), aneurysm size (P=0.0071), and RROC III immediate post-procedure (P =0.0086) in a model that also included bifurcation aneurysm (P=0.7788). Predictors of aneurysm retreatment at 1-year was rupture status (P <0.0001). Conclusions: Lesions treated with SMART System coils achieved low long-term retreatment rates. Clinical Trial Number (NCT): NCT02729740